Influence of MHD on Steady State Newtonian Fluid Flow in A vertical Channel With Porous Wall Using HAM - Jabr, Khalid (Iraqi Journal of Science, 2023)
The aim of this paper is to analyses steady state three-dimensional magnetohydrodynamic(MHD) flow of fluid injected uniformly into the vertical channel with porous wall through one side of the channel. The equations which were used to describe the flow are the momentum and energy equations, these equations were written to get their non-dimensional form. It is found that these equations are controlled by many dimensionless parameter, such as Hartmann number M, Reynolds number Re and Peclet number Pe. The homotopy analysis method(HAM) is employed to obtain a analytical solutions for velocity and heat transfer fields. The effect of each dimensionless parameters upon the normal and tangential velocity, pressure and temperature distributions are analyzed and shown about (15) graphs by using the Mathematica package